A potential role for the secretogranin II‐derived peptide EM66 in the hypothalamic regulation of feeding behaviour. (March 2017) - Trebak, F.; Dubuc, I.; Arabo, A.; Alaoui, A.; Boukhzar, L.; Maucotel, J.; Picot, M.; Cherifi, S.; Duparc, C.; Leprince, J.; Prévost, G.; Anouar, Y.; et al.
Abstract : EM66 is a conserved 66‐amino acid peptide derived from secretogranin II (SgII), a member of the granin protein family. EM66 is widely distributed in secretory granules of endocrine and neuroendocrine cells, as well as in hypothalamic neurones. Although EM66 is abundant in the hypothalamus, its physiological function remains to be determined. The present study aimed to investigate a possible involvement of EM66 in the hypothalamic regulation of feeding behaviour. We show that i.c.v. administration of EM66 induces a drastic dose‐dependent inhibition of food intake in mice deprived of food for 18 hours, which is associated with an increase of hypothalamic pro‐opiomelanocortin (POMC) and melanocortin‐3 receptor mRNA levels and c‐Fos immunoreactivity in the POMC neurones of the arcuate nucleus. By contrast, i.c.v. injection of EM66 does not alter the hypothalamic expression of neuropeptide Y (NPY), or that of its Y1 and Y5 receptors. A 3‐month high‐fat diet (HFD) leads to an important decrease of POMC and SgII mRNA levels in the hypothalamus, whereas NPY gene expression is not affected. Finally, we show that a 48 hours of fasting in HFD mice decreases the expression of POMC and SgII mRNA, which is not observed in mice fed a standard chow. Taken together, the present findings support the view that EM66 is a novel anorexigenic neuropeptide regulating hypothalamic feeding behaviour, at least in part, by activating the POMC neurones of the arcuate nucleus.